LOGICO-HYPOTHETICO-VERIFICATIF SEBAGAI METODA ILMIAH DALAM MENCARI ILMU PENGETAHUAN YANG BENAR - Rohendi , Acep (Yustitia, 2019)
Man's journey in finding the truth to overcome problems in his life, discussing various theories / flows in his time and continually developing complementary. Correlation of truth flow that emphasizes truth is in accordance with what is expected by humans or human experience. Arguments that are not in accordance with facts are not truth. Something is considered to be something that is in accordance with the facts (empirical). Contrary to this theory is the theory of Consistency, which confirms something that supports the truth that was previously questioned. The scientific method as a path of truth is used to get knowledge using Correspondence theory and Consistency theory. Combined theories of correspondence and consistency theory produce the term "Logico-hypothetico-verificatif" with all its advantages and disadvantages.